Etika Pembelajaran Perspektif KH. Hasyim Asy’ari dalam Kitab Adabul ‘Alim wal Muta’allim Serta Relevansinya terhadap Generasi-Z - Ramdani, Septian; Tafsir, Ahmad; Sukandar, Ahmad (CV. Media Publikasi Profesional, 2021)
The era of information and knowledge, which is marked by the placement of information technology and intellectual knowledge as the main capital in various fields of life, turns out to have a negative impact on the growth of ethics and character of the nation. The degradation of ethics, morals, attitudes and behavior is increasingly felt in various circles of society. This problem also afflicts educators. Therefore, it is necessary for educational actors to know and practice learning ethics. Because of this, many ideas have emerged regarding the concept of learning ethics, including the concept of learning ethics by KH. Hasyim Asy'ari written in his book Adabul 'Alim Wal Muta'allim. The theological foundation in this research is the Word of Allah SWT QS. Al-Kahf verse (18: 65-70). The philosophical foundation in this research is based on the philosophy of behaviorism. This research uses a qualitative research approach with the type of literature research (Library Research). The data in this study, researchers took data from primary sources, namely the book Adabul 'Alim Wal Muta'allim by KH Hasyim Asy'ari printed Maktabah Tsurots Islami PP. Tebuireng Jombang. Collecting data from this research is done by reviewing and reviewing the literature that contains verbal data in the form of words not in the form of numbers. Thus, the discussion in this research is applied by editing, reducing, presenting which then analyzes as well as identifies and grouping according to each chapter. This study aims to: (1) To find out and analyze the concept of ethics in learning from the perspective of KH. Hasyim Asy'ari in the book Adabul 'Alim Wal Muta'allim. (2) To find out and analyze the ethical relevance of perspective learning. KH. Hasyim Asy'ari in the book Adabul 'Alim Wal Muta'allim to the Z-generation. To be able to find out the results of this study, the author uses several steps, namely: (1) Content Analysis (Content Analysis) (2) Interpretation. This study resulted in (1) the concept of learning ethics from the perspective of KH. Hasyim Asy'ari in the book Adabul 'Alim Wal Muta'allim. The contents are student ethics and educator ethics. (2) The relevance of KH's perspective learning concept. Ash'ari in the book Adabul 'Alim Wal Muta'allim against Generation-Z. The concept of learning ethics from the perspective of KH. Hasyim Asy'ari has a fairly strong relevance to the context of education today or in the Z-generation era. Especially if it is associated with the ideal teacher profile as formulated in the PP. No. 74 of 2008 and the National Education Goals listed in Law Article 3 paragraph 1 Number 20 of 2003.